Nasirova, Ofelya - (:unkn) unknown (My University, 2026)
Ofelya Adil Nasirova graduated from the Azerbaijan University of Architecture and Construction (AzUAC) in 1998 with a Bachelor’s degree in Economics and Management of Construction. She began her professional career in accounting and subsequently joined AzUAC in 1997. Since 2000, she has been working at the Department of Marketing and Management, currently the Department of Economic Theory and Marketing, where she has held academic positions and has served as a Senior Lecturer since 2023. In 2018, she successfully defended her PhD dissertation, Ways to Enhance the Role of the Agricultural Sector in Ensuring Food Security in Azerbaijan. In 2020, she was awarded the degree of Doctor of Philosophy (PhD) in Economics by the Higher Attestation Commission under the President of the Republic of Azerbaijan. Dr. Nasirova is the author of 11 scientific articles, including 4 publications in internationally indexed journals, 15 conference papers, 10 conference abstracts, 2 course programmes, 2 methodological manuals, and 1 teaching manual. Her research interests include agricultural economics, food security, and the role of the agricultural sector in Azerbaijan.